What to call a dog? A review of the common names for Australian free-ranging dogs - Kreplins, T.; Gaynor, A.; Kennedy, M.; Baudains, C.; Adams, P.; Bateman, Bill; Fleming, P. (Surrey Beatty and Sons, 2018)
Wildlife research is informed by human values and interests, and these are reflected in, and reinforced by, the language used to describe particular species and animals. Examining factors that influence the use of common names of contentious taxa such free-ranging dogs is important, as naming can influence the design and reception of scientific studies. There are a range of common names for free-ranging dogs in Australian scientific literature but the most common names are 'dingoes' and 'wild dogs'. This review investigated influences on the terminology used to describe Australian free-ranging dogs in scientific studies from October 1952 to January 2018. Using a multidimensional scaling analysis, we tested the effects of several potential factors on terminology around Australian free-ranging dogs. We found a significant correlation between studies that reported on 'wild dog' control within livestock production-focussed papers and the use of the term 'dingo' and discussion of mesopredator release in conservation-related papers. There was a bias associated with author employment, with studies funded by a livestock production organisation more likely to employ 'wild dog' terminology. Year of publication and dingo purity within the locale of the study made a lesser contribution to differences in terminology. Our study explores the contextual factors that influence the choice of common names in scientific papers. Although referring to the same species, this review highlights that common terminology within scientific papers is reliant on the discussion of mesopredators release, control programs and the paper's context.